Prevalence of Shiga toxin‐producing Escherichia coli in pasture‐based dairy herds. (1st February 2019) - Ross, C.M.; Rapp, D.; Cave, V.M.; Brightwell, G.
Abstract: Shiga toxin‐producing Escherichia coli strains (STEC) are food‐borne pathogens. While E. coli O157:H7 is commonly associated with cattle, less is known about the prevalence of non‐O157 STEC serogroups in bovines. This study evaluated the prevalence and virulence status of O157:H7 and six E. coli O‐serogroups (O26, O103, O45, O145, O121, O111) in New Zealand dairy farms using molecular as well as culture‐based methods. Fresh farm dairy effluent (FDE) ( n = 36) and composite calf faeces ( n = 12) were collected over three samplings from 12 dairy farms. All seven target serogroups were detected through molecular techniques. Of the 202 isolates which were serologically confirmed following traditional culturing and immunomagnetic separation (IMS), O103, O26, O45 and O121 were the most common serogroups, being found in 81, 47, 42 and 32% of the FDE and in 17, 33, 25 and 9% of the calf faeces respectively. The majority (157/202) of the isolates were negative for stx and eae virulence genes. The prevalence of the seven target STEC was low, and only nine O26 isolates (4%) were recovered from four of the farms. The study has highlighted the need for improving the isolation of Top 7 STEC from the stx ‐negative populations present in fresh dairy effluent and calf faeces. Significance and Impact of the Study: Shiga toxin‐producing Escherichia coli (STEC) are important food‐borne pathogens that can cause severe illness in humans. Cattle are asymptomatic reservoirs for STEC, and transmission to humans can be by consumption of food products or water contaminated with cattle faeces. Our study investigated the prevalence of O157:H7 and six E. coli serogroups of STEC (O26, O103, O45, O145, O121, O111) over time in the dairy reservoir and increases the knowledge and understanding of these pathogens on pasture‐based farms. Such information is required to develop risk‐assessment models aiming at limiting transmission of these STEC to human.